Design and control analysis of a deployable clustered hyperbolic paraboloid cable net. (15th March 2023) - Ma, Shuo; Lu, Kai; Chen, Muhao; Skelton, Robert E.
Highlights: Proposed a deployable clustered hyperbolic paraboloid cable net design. Studied form-finding, prestress design, deployment process, and shape control of the cable net. Compared open-loop and closed-loop control by numerical and experimental tests. Abstract: This paper presents an analytical and experimental design and deployment control analysis of a hyperbolic paraboloid cable net based on clustering actuation strategies. First, the dynamics and statics for clustered tensegrity structures (CTS) are given. Then, we propose the topology design of the deployable hyperbolic paraboloid cable net. The deployability of the cable net is achieved by using clustered cables. It is shown that the clustered cables significantly reduce the number of actuators required for control. The deployment trajectory and actuation prestress in the cables are designed to ensure the tensions are feasible during the deployment process. Then, we compare the deployment analysis's open-loop and closed-loop control strategies. Finally, a lab-scale model is constructed to validate the actuation laws. We test the static performance and deployment process of the experimental model. Results show that the closed-loop control approach is more stable and smoother than the open-loop one in the deployment process. The approaches developed in this paper can also be used for various deployable tensegrity structures.